Genome-Wide Association and Mendelian Randomization Analysis Reveal the Causal Relationship Between White Blood Cell Subtypes and Asthma in Africans - Soremekun, Opeyemi; Soremekun, Chisom; Machipisa, Tafadzwa; Soliman, Mahmoud; Nashiru, Oyekanmi; Chikowore, Tinashe; Fatumo, Segun (Frontiers in Genetics, 2021)
Background: White Blood Cell traits (WBC) and their subtypes such as basophils count (Bas), eosinophils count (Eos), lymphocytes count (Lym), monocytes count (Mon) and neutrophils counts (Neu) are known to be associated with diseases such as stroke, peripheral arterial disease, and coronary heart disease. Methods: We meta-analyze summary statistics from genome-wide association studies in 17,802 participants from the African Partnership for Chronic Disease Research (APCDR) and African ancestry individuals from the Blood Cell Consortium (BCX2) using GWAMA. We further carried out a Bayesian fine mapping to identify causal variants driving the association with WBC subtypes. To access the causal relationship between WBC subtypes and Asthma, we conducted a two-sample Mendelian Randomization (MR) analysis using summary statistics of the Consortium on Asthma among African Ancestry Populations (CAAPA: ncases = 7009, ncontrol =7645) as our outcome phenotype. Results: Our metanalysis identified 269 loci at a genome-wide significant value of (P = 5 x 10-9) in a composite of the WBC subtypes while the Bayesian fine-mapping analysis identified genetic variants that are more causal than the sentinel Single nucleotide polyphormism (SNP). We found for the first time five novel genes (LOC126987/MTCO3P14, LINC01525, GAPDHP32/HSD3BP3, FLG-AS1/HMGN3P1, and TRK-CTT13-1/MGST3) not previously reported to be associated with any WBC subtype. Our MR analysis showed that Mon (IVW estimate = 0.38, CI: 0.221, 0.539, P < 0.001), Neu (IVW estimate = 0.189, CI: 0.133, 0.245, P < 0.001), and, WBCc (IVW estimate = 0.185, CI: 0.108, 0.262, P < 0.001) are associated with increased risk of asthma. However, there was no evidence of causal relationship between Lym and asthma risk. Conclusion: This study provides insight into the relationship between some WBC subtypes and Asthma and potential route in the treatment of Asthma and may further inform a new therapeutic approach.